Pemberdayaan Madrasah Diniyah: Meningkatkan Kualitas Pendidikan Agama Islam - Nurlaela, Tuti; Nasucha, Juli Amaliya; Rofiq, Muhammad Husnur (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This study explores endeavors aimed at enhancing the caliber of Islamic religious education at SMK N 1 Bangli by fostering collaboration with Madrasah Diniyah Al-Hidayah. Data for the research was gathered through on-site observations, interviews, and document analysis. The findings indicate that Madrasah Diniyah plays a crucial role in augmenting comprehension of religious materials and elevating the standard of Islamic religious education within the SMK N 1 Bangli setting. This contribution is manifested through the cultivation of ethical values, curriculum enhancement, teacher capacity building, extension of instructional hours, reinforcement of worship practices, oratory skills development, and provision of facilities and infrastructure. These endeavors are in line with the principles of Islamic education encompassing moral upbringing, individual enlightenment, and societal enrichment. The research outcomes demonstrate a positive impact on enhancing the quality of Islamic religious education across cognitive, affective, and psychomotor domains. These findings corroborate earlier research results highlighting the pivotal role of Islamic religious education in instilling moral virtues, fostering noble character, and promoting public awareness regarding the significance of Islamic education. The collaboration between SMK N 1 Bangli and Madrasah Diniyah Al-Hidayah serves as a potential model for other educational institutions seeking to enhance the quality of Islamic religious education through fruitful partnerships with religious educational establishments.